Methodological basis of firm financial risk management - Nabiyev Mahayad Anvar (Technium Social Sciences Journal, 2020)
The purpose of this article is to summarize the theoretical, methodological and methodological foundations of financial risk management in firms in modern conditions. The methodological basis of the research is the works of economists devoted to financial risk management. Research novelty. Various methods are presented in the economic literature for assessing financial risks. The introduction of modern methods of systematic and consistent analysis of the financial risk management of a firm is the main novelty of this study. Conclusion. Based on the current liquidity ratio of the company’s financial condition and the assessment of borrowed funds in terms of liabilities, a two-factor model is investigated, and on the basis of working capital in terms of assets, return on assets (ratio of retained earnings to assets), profitability (ratio of operating income to assets), market value of shares by the ratio of liabilities and profitability of assets (profit by ratio to assets), a five-factor model is investigated. In the economic literature, it is considered appropriate to use the revised Altman model in developing countries.